Prevalence of over the counter (OTC) medicine use and the potential of drug-drug interactions with concomitant prescription medicine use at an old age home in Johannesburg - Dube, Sandile Olivia (My University, 2021)
Background: The prevalence of the use of OTC medicines in the elderly in South Africa is understudied. The elderly are known to use OTC medicines in combination with their chronic medicines. To prevent drug-drug interactions and adverse drug reactions, understanding the commonly used OTC medicines amongst the elderly will assist in preventing complications and reducing healthcare costs for these patients. Objectives: To describe utilization patterns of OTC medicines, perceptions and the potential of drug-drug interactions from OTC medicine use amongst the elderly at an old age home. Method: The study was a cross-sectional, quantitative study. One hundred and six questionnaires were completed by study participants, between the ages of 65 to 85. The study was conducted at Summerfield Park Methodist Home, in Johannesburg between December 2019 ± August 2020. A questionnaire was used as the data collection tool. Data were analyzed using Microsoft® Excel. Results: Eighty six and a half percent (95% CI, 83.7% - 90.0%) of the study participants used at least one OTC medicine. Severe drug-drug interactions made up 15.5% of those reported. Forty five percent of the study participants responded that they use OTC medicines at the first sign of illness. Conclusion: The prevalence of use of OTC medicines was high and there is a general lack of knowledge of their safety and efficacy. The potential for drug-drug interactions between OTC and prescription medicines exists and healthcare providers need to have practice good history taking
A research report submitted to the Faculty of Health Sciences at the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Pharmaceutical Affairs)